A Quantitative Study of Intimate Partner Violence Context: Is Self-Compassion Related to Sexual Esteem? - Nabila, Tazkia Nada; Larue, Chloe Dwi Nuariani (Developmental and Clinical Psychology, 2023)
Intimate partner violence (IPV) is defined as physical, psychological, or sexual violence perpetrated by a partner. This conduct is harmful and has long-term negative consequences for people who encounter it, particularly psychological illnesses. This has an impact on judgment, self-satisfaction with sexuality, and sexual function. This can influence how people evaluate their relationships and sexuality, how individuals assess their worth in a sexual context, which is thought to be related to self-compassion in individuals. This study drew 227 participants, consisting of men and women aged 20 to 30 who have been or are now in a dating relationship for at least one year. Purposive sampling was used to collect the research sample. The Conflict Tactic Scale Revised-2 (CTS-2) measurement tool, the Multidimensional Sexual Self-Concept Questionnaire (MSSCQ) subscale sexual esteem, and the Self-Compassion Scale were utilized for data collection. The direction of the association between variables is positive, indicating that the higher the level of self-compassion ability, the higher the level of sexual-esteem capacity in persons, and vice versa.